Assessment of the anti-biofilm effect of UV-C irradiation (254 nm) against healthcare associated infections related microorganisms - Palma, Francesco; Díaz-Navarro, Marta; Visedo, Andrés; Sanz-Ruíz, Pablo; Brandi, Giorgio; Schiavano, Giuditta Fiorella; Guembe, María (Frontiers in Microbiology, 2025)
IntroductionBiofilm-related Multidrug Resistance (MDR) is a major problem in healthcare-associated infections (HAI). Hospital surface decontamination is essential to ensure the safety of patients and to eliminate the dissemination of MDR pathogens. New eco-friendly decontamination technologies, such as UV-C irradiation, are only gaining popularity now, but their use against the biofilm of common microorganisms causing HAI has not been properly assessed. We aimed to assess the efficacy of UV-C irradiation (254 nm) in a 2-phase study by assessing its anti-biofilm effect against sessile cells from microorganisms of hospital interest.MethodsThe following strains were tested: methicillin-susceptible Staphylococcus aureus (MSSA) (ATCC 29213), methicillin-resistant Staphylococcus aureus (MRSA) (ATCC 43300), Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 15442, and Candida albicans (ATCC 14053), and a clinical strain of methicillin-resistant Staphylococcus epidermidis. First, the tested strains' UV-susceptibility was evaluated through irradiation tests on plates using different UV doses, considering both planktonic and 24 h-biofilm states. Second, the anti-biofilm effect of UV-C was evaluated on stainless steel discs contaminated with a 24 h-biofilm of each strain.ResultsWith a UV dose of 946.7 mJ/cm2, the UV-C irradiation on MSSA ATCC 29213, MRSA ATCC 43300, and MRSE biofilm showed a log10 reduction of 4.34 ± 0.70, 4.70 ± 0.60, and 4.85 ± 0.98, respectively, while C. albicans ATCC 14053 showed higher UV-resistance in 24 h-biofilm state, being the log10 reduction of 3.17 ± 0.08. Against Gram negative bacteria biofilm, a UV dose of 467.8 mJ/cm2 was enough to achieve a microbial titer < 1 CFU/mL. Regarding the 24 h-biofilm on discs, a log10 reduction >3 logs was achieved with all microorganisms applying a UV dose of 946.7 mJ/cm2.ConclusionThe application of UV-C irradiation could be a valid additional approach in the management of biofilm HAI.